Adherence to antenatal care among rural pregnant women in Lagos, Nigeria (2021)
Background: The benefits of early and frequent antenatal care visits include early prevention, detection, treatment of potential pregnancy complications and the reduction of maternal mortality related to these complications. Despite these benefits being explained to them, the majority of pregnant women in developing countries, including Nigeria, do not adhere to antenatal care, as they do not attend the recommended number of antenatal care appointments. Previous research has shown that urban women (84%) are more likely than rural women (56%) to receive antenatal care from a skilled provider. This study examined adherence to antenatal care among rural pregnant women in Lagos, Nigeria. Methods: This was a cross-sectional descriptive study using multistage sampling to select 600 pregnant women from rural areas of Lagos. A self-structured questionnaire was used to collect participants' sociodemographic data, knowledge of antenatal care, and adherence to antenatal care. Data were analysed and presented using descriptive and inferential statistics. Chi-square tests were used to assess the association between adherence to antenatal care and knowledge about antenatal care, and logistic regression was used to test the association between participants' characteristics and adherence to antenatal care, with P<0.05 being considered significant. Results: Participants were between 15 and 49 years old and 96.2% were married. The majority of participants had poor knowledge of antenatal care (57.1%), and low adherence to antenatal care (71.7%). However, 73.9% had the overall perception that there were benefits to attending antenatal care. No significant relationship was found between participants' knowledge of and adherence to antenatal care (P=0.32). Occupation was significantly associated with adherence to antenatal care (P=0.03). The majority (54.4%) indicated that perceived barriers are the major cause of non-adherence to antenatal care. Conclusions: Addressing perceived barriers to antenatal care attendance should increase adherence to antenatal care, especially in rural areas of Lagos.